Effective communication: Core to promoting respectful maternity care for disabled women. (January 2023) - Collins, Bethan; Hall, Jenny; Hundley, Vanora; Ireland, Jillian
Abstract: Objective: Previous research highlights that disabled women have less choice, control and respect of their dignity during pregnancy, childbirth and parenting. The experience of dignity and respect during pregnancy and childbirth for those with physical and sensory disability in the UK and Ireland is explored. Design, setting and participants: Narrative, semi-structured telephone and Skype interviews were conducted with ten disabled women in the UK and Ireland. Interviews were audio-recorded and transcribed verbatim. Intra- and inter-thematic analysis was undertaken, beginning with a process of open coding. As themes developed, a process of constant comparison was used. Findings: The key finding is that effective communication with women was perceived to best respect the women's dignity in childbirth. This meant enabling women to feel heard, enabling women to make informed decisions about their care and providing individualized care. The single most important factor that enabled this communication was continuity of carer. Key Conclusions: The factor that most promoted maternity care that was perceived to be respectful was effective communication. This is not so different in other parts of the world, or for non-disabled women, however care providers should be particularly careful to enable good communication with disabled women.